Cyber Legal Protection for Consumers in Cross-Border E-Commerce Transactions in the ASEAN Region - Edy Krispono; Ahmad Redi (Greenation International Journal of Law and Social Sciences, 2025)
This article discusses cyber legal protection for consumers in cross-border e-commerce transactions in the ASEAN region, focusing on an analysis of Indonesian national regulations and the ASEAN regional framework. The rapid development of cross-border e-commerce brings significant opportunities for digital commerce, but also presents serious challenges in consumer protection, particularly regarding transaction security, information transparency, misuse of personal data, and cross-border dispute resolution mechanisms. Indonesia already has several relevant regulations, such as Government Regulation Number 80 of 2019 regarding Commerce Through Electronic Systems, Law Number 1 of 2024 concerning Electronic Information and Transactions, Law Number 8 of 1999 concerned Consumer Protection, and Law Number 27 of 2022 concerning Personal Data Protection. Although these regulations provide a basic framework, they are still limited in nature and cannot address the complexities of cross-border transactions. At the regional level, ASEAN has issued the ASEAN Agreement on E-Commerce, which encourages the establishment of a safe, fair, and inclusive digital commerce ecosystem. However, its implementation still faces challenges in legal harmonization, differences in consumer protection standards, and limitations in cross-border dispute resolution mechanisms. Therefore, strategic steps are needed to harmonize regulations across ASEAN countries, establish a regional dispute resolution forum, and enhance cooperation between supervisory authorities in the areas of digital trade and personal data protection. It will ensure more effective cyber legal protection for consumers in cross-border e-commerce transactions, bolster public trust, and strengthen digital economic integration in the ASEAN region.